Sanctum - Roux, Madeleine, 1985- (Harper, an imprint of HarperCollinsPublishers, 2014)
"Plagued by nightmares from their summer in the Brookline asylum, Dan, Abby, and Jordan return to New Hampshire College for a prosective students weekend, only to find themselves caught in a dark and dangerous mystery"--